2020
DOI: 10.1101/2020.05.19.104455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis identifies genetic effects on reproductive success and ongoing natural selection at theFADSlocus

Abstract: Identifying genetic determinants of reproductive success may highlight mechanisms underlying fertility and also identify alleles under present-day selection. Using data in 785,604 individuals of European ancestry, we identify 43 genomic loci associated with either number of children ever born (NEB) or childlessness. These loci span diverse aspects of reproductive biology across the life course, including puberty timing, age at first birth, sex hormone regulation and age at menopause. Missense alleles in ARHGAP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…Interestingly, we identified a positive genetic correlation between male fertility and subjective well-being and a negative genetic correlation with the sibling effect. We identified six of the previous 28 statistically independent loci for fertility, and one of the 16 loci for childlessness 29 . In addition, we identified a novel locus on chromosome 9 that is associated with female fertility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, we identified a positive genetic correlation between male fertility and subjective well-being and a negative genetic correlation with the sibling effect. We identified six of the previous 28 statistically independent loci for fertility, and one of the 16 loci for childlessness 29 . In addition, we identified a novel locus on chromosome 9 that is associated with female fertility.…”
Section: Discussionmentioning
confidence: 99%
“…The heritability of number of children ever born has been estimated to be between 0.24-0.43 27 , and the variance explained by common genetic variants (SNP based heritability) is estimated to be approximately 10% 28 . Although there have been two GWAS previously conducted on number of children born 23,29 , no study to date has estimated the conditional male, female and sibling genetic effects at individual genetic loci. Both previous studies observed significant genetic correlations for the number of children between men and women (Barban and colleagues 23 : r g =0.97, SE=0.095; Mathieson and colleagues 29 : r g =0.74, 95%CI=0.66-0.82), which our findings from the conditional analysis are consistent with (r g =0.871, SE=0.023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 We construct three new scores for our four outcomes, that is, age at first sexual intercourse, age at first birth, and completed fertility (which is used also for childlessness). These scores are based on results from the most recent fertility GWAS, including Barban et al (2016), Mathieson et al (2020), andMills et al (2021). Evidence presented in these studies implicates mechanisms related to reproductive health, puberty timing, and evolutionary fitness in the biological pathways that link the scores to fertility phenotypes.…”
Section: Polygenic Scoresmentioning
confidence: 99%
“…We emphasize three. First, since fertility traits and outcomes are known to have some of the highest degrees of polygenicity of any complex phenotype reflecting the influence of many different genes and consistent with a genetic architecture that may be influenced by negative selection (Visscher et al, 2008;O'Connor et al, 2019;Mathieson et al, 2020), polygenic scores acknowledge that each individual falls on a continuum of genetic predisposition which results from small contributions of multiple genetic variants. By contrast, single variants can only be weak predictors of any given fertility phenotype.…”
Section: Opportunities Limitations and Interpretationmentioning
confidence: 99%